Quantitative sensory testing profiles in chronic back pain are distinct from those in fibromyalgia - Blumenstiel, Klaus; Gerhardt, Andreas; Rolke, Roman; Bieber, Christiane; Tesarz, Jonas; Friederich, Hans-Christoph; Eich, Wolfgang; Treede, Rolf-Detlef (The clinical journal of pain, 2011)
Objectives - Alterations in the central nervous system leading to higher pain sensitivity have been shown in both chronic back pain (CBP) and fibromyalgia syndrome (FMS). The aim of this study was to disclose commonalities and differences in the pathophysiology of FMS and CBP. - Methods - We used the quantitative sensory testing protocol of the German Research Network on Neuropathic Pain to obtain comprehensive profiles of somatosensory functions. The protocol comprised thermal and mechanical detection and pain thresholds, vibration thresholds, and pain sensitivity to sharp and blunt mechanical stimuli. We studied 21 FMS patients (mean pain duration: 13.4 y), 23 CBP subjects (mean pain duration: 15.9 y), and 20 healthy controls (HCs). Each participant received the test battery on the back and on the dorsal hand (pain-free control site). - Results - On the back, FMS patients showed increased thermal and mechanical pain sensitivity compared with HCs and CBP participants. On the hand dorsum, FMS patients showed higher mechanical pain sensitivity compared with CBP participants and HCs and higher cold pain sensitivity compared with HCs. CBP participants showed increased pressure pain sensitivity and lower vibration sensitivity on the back, but no significant differences on the hand dorsum compared with HCs. - Discussion - FMS patients showed increased sensitivity for different pain modalities at all measured body areas, suggesting central disinhibition as a potential mechanism. CBP participants in contrast, showed localized alterations within the affected segment possibly due to peripheral sensitization.